Long-term follow-up of the RESONATE phase 3 trial of ibrutinib vs ofatumumab - Byrd, John C.; Hillmen, Peter; O'Brien, Susan; Barrientos, Jacqueline C.; Reddy, Nishitha M.; Coutre, Steven; Tam, Constantine S.; Mulligan, Stephen P.; Jaeger, Ulrich; Barr, Paul M.; Furman, Richard R.; Kipps, Thomas J.; et al. (Blood, 2019)
Ibrutinib, a once-daily oral inhibitor of Bruton tyrosine kinase, has greatly improved outcomes for patients with chronic lymphocytic leukemia (CLL). The phase 3 RESONATE trial, which compared single-agent ibrutinib to ofatumumab in high-risk, relapsed patients with CLL, provided support for approval of ibrutinib in the United States and Europe. We describe long-term follow-up of patients treated in RESONATE, where continued superiority of progression-free survival (PFS) (hazard ratio [HR], 0.133; 95% confidence interval [CI], 0.099-0.178) was observed. Overall survival benefit continues (HR, 0.591; 95% CI, 0.378-0.926), although with decreased magnitude relative to that seen before crossover to ibrutinib was implemented for patients on ofatumumab (HR, 0.426; 95% CI, 0.220-0.823). Notably, overall response to ibrutinib increased over time, with 91% of patients attaining a response. The PFS benefit with ibrutinib was independent of baseline risk factors, although patients with ≥2 prior therapies had shorter PFS than those with <2 prior therapies, and the presence of TP53 or SF3B1 mutations showed a trend toward shorter PFS vs without these factors. Median duration of ibrutinib was 41 months, with 46% remaining on treatment at a median follow-up of 44 months. Grade ≥3 adverse events generally decreased over time, causing only a small proportion of patients to cease therapy. Ibrutinib was discontinued due to progressive disease in 27% of patients. This long-term study provides support for sustained efficacy and safety of ibrutinib in relapsed/refractory CLL and consideration of study provisions that allow crossover to investigational therapy when benefit has been clearly demonstrated. This trial was registered at www.clinicaltrials.gov as #NCT01578707. •Extended ibrutinib treatment showed sustained PFS in previously treated patients with CLL, including those with high-risk cytogenetics.•Overall survival outcomes were sustained and no long-term safety signals have emerged with 4 years of follow-up on ibrutinib treatment. [Display omitted]